2016
DOI: 10.1111/imm.12630
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages transfer antigens to dendritic cells by releasing exosomes containing dead‐cell‐associated antigens partially through a ceramide‐dependent pathway to enhance CD4+ T‐cell responses

Abstract: SummaryDefects in rapid clearance of apoptotic cells lead to an accumulation of dead cells (late apoptotic or secondary necrotic cells), which results in an aberrant immune response. However, little is known about whether and how macrophages (Mφs) cooperate with dendritic cells (DCs) in the presentation of dead-cell-associated antigens in this process. By transferring high numbers of dead cells to mimic a failure of apoptotic cell clearance in vivo, we found that Mφs and neutrophils were the predominant phagoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 47 publications
(108 reference statements)
0
34
0
Order By: Relevance
“…Albeit, as EVs contain surface molecules such as HLA‐DR, we figured that the cellular interaction might be subject‐specific and thus question the use of DCs from different human donors. It has however been shown several times that miRNAs can be functionally transferred to target cells and that DC function is modulated by EVs . Thus, it is intriguing to speculate that sEVs‐associated epithelial miRNAs are involved in regulating the immune responses by underlying DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit, as EVs contain surface molecules such as HLA‐DR, we figured that the cellular interaction might be subject‐specific and thus question the use of DCs from different human donors. It has however been shown several times that miRNAs can be functionally transferred to target cells and that DC function is modulated by EVs . Thus, it is intriguing to speculate that sEVs‐associated epithelial miRNAs are involved in regulating the immune responses by underlying DCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has however been shown several times that miRNAs can be functionally transferred to target cells [48][49][50][51][52][53] and that DC function is modulated by EVs. [54][55][56] Thus, it is intriguing to speculate that sEVs-associated epithelial…”
Section: Discussionmentioning
confidence: 99%
“…For example, colorectal cancer exosomes transfer mRNAs, which promote endothelial cell proliferation and facilitate angiogenesis [22], whereas glioblastoma-derived exosomes promote tubule formation by recipient endothelial cells [23]. Furthermore, tumour exosomes secrete factors that suppress natural killer cell activity and induce T-cell apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…As in A, before n-SMase action SM stabilizes membrane structure, while Cer production by n-SMase induces spontaneous negative curvature to the membrane of endosomes, thus promoting the formation of internal vesicles inside MVBs. Subsequent in vitro works reported that, while exogenous cell permeable C6 Cer dose-dependently increases the number of exosomes released from multiple myeloma cells (51), pharmacological or genetic block of n-SMase inhibited packaging of the prion protein into exosomes (52) and reduced exosome release among others in HEK cells (53), T cells (54), N2a cells (55), astrocytes (56), microglia (57), macrophages (58), hepatocytes (59), and multiple myeloma cells (51). Also, in vivo, in the brain and serum of 5XFAD mice, a transgenic model of Alzheimer's disease (AD), the n-SMase inhibitor, GW4869, decreased exosome concentration (60).…”
Section: Downloaded Frommentioning
confidence: 99%